Identification of Novel Genes Involved in Escherichia coli Persistence to Tosufloxacin - Li, Tuodi; Wang, Juan; Cao, Qianqian; Li, Fei; Han, Jiangyuan; Zhu, Bingdong; Zhang, Ying; Niu, Hongxia (Frontiers in Cellular and Infection Microbiology, 2020)
Persisters are metabolically quiescent phenotypic variants of the wild type that are tolerant to cidal antibiotics, and the mechanisms of persister formation and survival are complex and not completely understood. To identify genes involved in persistence to tosufloxacin, which has higher activity against persisters than most other quinolones, we screened the E. coli KEIO mutant library using a different condition from most persister mutant screens (6h) with a longer exposure of 18h with tosufloxacin. We identified 18 mutants（acrA, acrB, ddlB, dnaG, gltI, hlpA, lpcA, recG, recN, rfaH, ruvC, surA, tatC, tolQ, uvrD, xseA and ydfI）that failed to form tosufloxacin tolerant persisters. Among them, gltI, hlpA, ruvC, ddlB, ydfI and tatC are unique genes involved in E. coli persistence to tosufloxacin which have not been reported before. Furthermore, deletion mutants in genes coding periplasmic proteins (surA, lpcA, hlpA and gltI）had more defect in persistence to tosufloxacin than the other identified mutants, with surA and lpcA mutants being the most prominent. The “deep” persister phenotype of surA and lpcA mutants was further confirmed both in vitro and in vivo. Compared with the wild type strain E. coli BW25113 in vitro, the persister phenotype of the surA and lpcA mutants was decreased more than 100-1000 fold in persistence to various antibiotics, acidic, hyperosmotic and heat conditions. In addition, in both stationary phase bacteria and biofilm bacteria infection mouse models, the surA and lpcA mutants had lower survival and persistence than the parent uropathogenic strain UTI89, suggesting that the in vitro identified persister mechanisms (surA and lpcA) are operative and valid for in vivo persistence. Our findings provide new insight into the mechanisms of persister formation and maintenance under tosufloxacin and will likely provide novel therapeutic and vaccine targets for developing more effective treatment and prevention of persistent E. coli infections.